Chemical and physical properties of the Kizildag olivines. A giant olivine deposit, Antalya, SW Turkey - Zedef, V; Doyen, A; Oncel, MS; Sogut, AR; Koseleli, T; Kocak, K (Ofioliti, 2004)
The Kizildag olivine deposit is found within the Kizildag ultramafics. The main source of the olivine are the dunites, which are located in the ultramafics. The chemical and mineralogical composition and the physical properties of the studied samples are relatively uniform. The main component of the dunites is forsteritic olivine (Mg2SiO4), which consists of 48.75% MgO, 42.31% silica and 7.21% Fe2O3, The average expansion rate and ignition loss is 1.18% and 0.96% respectively. These percentages satisfy the requirements of the iron and steel industry, as well as meeting acceptable refractory standards. The reserve of the Kizildag olivine deposits is estimated to be 9 billion (9,000,000,000) tons, which is comparable to the largest known olivine deposits of Aheim (Norway). The olivine of Kizildag can be exported to international markets, for the port of Antalya is situated 120 km from the deposits. The main disadvantage is the failure of the domestic market to recognize the olivine as a valuable resource.
Keywords: olivine; chemistry; physical properties; Kizildag. Turkey